Broadening the Scope: Low and High Temperature Geothermal Utilization in Iceland - Ragnarssdóttir, Kolbrún Ragna; Ólafsson, Dagur Ingi; Haraldsdóttir, Helen Ósk; Mintsa Do Ango, André (Zenodo, 2021)
celand is sitting on a vast amount of various energy resources. The high temperature geothermal systems are being used for both electrical generation and direct use. Due to the accessibility of this high temperature energy source there is generally less focus on fully utilizing the low temperature systems. Presently, the low temperature systems are used for direct use such as house heating and growing of produce. The innate differences between these areas result in these different utilization capabilities and general requirements. The MEET project looks to increase the utilization of low temperature systems in Europe for electricity production through binary cycles designed to be more compact, have higher efficiency and lower cost. The use of such cycles could greatly increase the capability of utilizing these resources more efficiently and lead to greater development of renewable energy. In this paper the different conditions in low temperature areas compared to high temperature areas are looked at. The high temperature Reykjanes and low temperature Grásteinn II areas are focused on specifically as these locations will be used for testing of Organic Rankine Cycles (ORC) within the MEET project. Material requirements can vary between areas giving grounds for different material being needed and this will be looked with components for binary cycles in mind.